Strategi Pengembangan Pantai Tamarunang sebagai Obyek Wisata Pantai di Kabupaten Jeneponto - Fajrin Mappa; Baharuddin Koddeng; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
Jeneponto, located in South Sulawesi, East Indonesia, has natural potential diversity particularly in tourism sector which can be developed to improve the revenue. Tamarunang Beach in Jeneponto has potency to tourism region development in accordance with the RTRW Kabupaten Jeneponto 2010-2030. Tamarunang Beach has many tourism attraction potentials. Development strategy of the Tamarunang Beach was formulated by using SWOT or IFAS and EFAS analysis. Then, zoning analysis was conducted by divide the area into several segments to apply the strategy into the zones base on its potential. The policy was arrange from the previous analysis including development of tourism attraction zone and coastal tourism facilities in Tamarunang.